Analisis Kesiapan Mahasiswa Pendidikan Teknik Bangunan untuk Menjadi Guru - Natsir, Taufiq; Ishak, Ishak; Zalsabilah, Nur (Journal of Comprehensive Science, 2024)
This research was conducted in the Building Engineering Education Study Program. The purpose of this study is to analyze the understanding of Building Engineering Education students towards the subject matter to be taught at SMK. Evaluate the understanding possessed by Building Engineering Education students about the teaching profession. Identify the pedagogical skills of Building Engineering Education students. This research is a quantitative approach research with a descriptive method. The results of the Kolmogorov-Smirnov Test normality test obtained a sig of 0.70. Because the significance value is greater than 0.05, it can be concluded that the residual value of the X variable data is normally distributed. showed that most of the students' understanding of the subject matter taught (X1) was high (54.84%), showing that most of the students' understanding of the teaching profession (X2) was high (48.40%), showing that most of the students' pedagogical skills (X3) were high (61.30%), students' understanding of the subject matter to be taught at SMK There were 54.84% of students showing a good understanding of the subject matter to be taught at SMK. Student understanding of the teaching profession 48.40% of students who have a high interest in becoming teachers. There are 61.30% of students who have the necessary pedagogical skills in the learning process.